The NCEP and ERA-Interim reanalysis temperature and humidity errors and their relationships with atmospheric boundary layer in the Tibetan Plateau - Che, Junhui; Zhao, Ping (Frontiers in Earth Science, 2023)
The lack of sounding observations in the western Tibetan Plateau (TP), the highest terrain in the world, has resulted in few efforts to the evaluate the quality of the atmospheric reanalysis results above the ground in this region. Using the sounding observations from the Third Tibetan Plateau Atmospheric Scientific Experiment during 2013-2015, the NCEP and ERA-Interim reanalysis temperature and humidity fields over the TP are evaluated and the characteristics of the reanalysis Atmospheric Boundary Layer (ABL) height are utilized to explain the reasons for the differences between the western and eastern TP. The results show that the NCEP and ERA-Interim reanalysis temperature and humidity products generally have larger errors at low level such as 500 hPa in the western TP (WTP) than in the eastern one (ETP) at 12:00 UTC. However, this difference is small at 00:00 UTC. Further analysis reveals that the temporal and spatial variations of temperature and humidity errors at low level are closely associated with the differences in the terrain and ABL between the western and eastern TP. In the early morning when the ABL height is low over the TP, the 500 hPa pressure level in both the WTP and ETP significantly above the top of ABL, with weak spatial variations of temperature and humidity errors. However, in the late afternoon when the larger increase in the ABL height over the WTP than over the ETP, the 500 hPa pressure level is located inside the ABL in the WTP, and is still above the ABL in the ETP, making significant regional differences of these errors.